2D Sin-Cos-Henon Map for Color Image Encryption with High Security. (4th August 2022) - Cheng, Zhiqiang; Wang, Wencheng; Dai, Yuezhang; Li, Lun
Abstract : In this paper, a high security color image encryption algorithm is proposed by 2D Sin-Cos-HÃ©non (2D-SCH) system. A new two-dimensional chaotic system which is 2D-SCH. This system is hyperchaotic. The use of the 2D-SCH, a color image encryption algorithm based on random scrambling and localization diffusion, is proposed. First, the secret key is generated by SHA512 through plaintext. As the initial value of the 2D-SCH system, the secret key is used to generate chaotic sequences. Then, the random scrambling is designed based on chaotic sequences. Finally, a pair of initial points is generated by the secret key; the image diffuses around this point. The ciphertext is obtained by a double encryption. Different from the traditional encryption algorithm, this paper encrypts three channels of color image simultaneously, which greatly improves the security of the algorithm. Simulation results show that the algorithm can resist various attacks.